1985
DOI: 10.1111/j.1528-1157.1985.tb05670.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Abilities of Children with Epilepsy

Abstract: One hundred eighteen epileptic children, aged 6-15 years, underwent detailed neuropsychological testing including the Wechsler Intelligence Scale for Children-Revised and the age-appropriate Halstead-Reitan battery. Eight had classical absence seizures only, eight had classic absence seizures and generalized tonic-clonic seizures, 30 had generalized tonic-clonic seizures only, 31 had partial seizures only, 20 had partial seizures and generalized seizures, 15 had atypical absence seizures, and five had minor mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
131
2
15

Year Published

2000
2000
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(157 citation statements)
references
References 11 publications
9
131
2
15
Order By: Relevance
“…Many studies of cognitive function in children with epilepsy have shown that their mean test scores were below that of the particular test used (21)(22)(23) and that even children with epilepsy but with no known neurologic disorder obtained lower IQ scores (24,25). Although it has been reported that children with epilepsy might have normal IQs (26) or that their IQs were not significantly different from controls (27), neuropsychological defects are not rare in children with idiopathic epilepsy who have normal IQs (26,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of cognitive function in children with epilepsy have shown that their mean test scores were below that of the particular test used (21)(22)(23) and that even children with epilepsy but with no known neurologic disorder obtained lower IQ scores (24,25). Although it has been reported that children with epilepsy might have normal IQs (26) or that their IQs were not significantly different from controls (27), neuropsychological defects are not rare in children with idiopathic epilepsy who have normal IQs (26,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The great variability in the academic achievement and neuropsychological functioning of children with epilepsy relates to many factors, including seizure type, severity and frequency of seizures, level of control of the seizures achieved through treatment, age of onset, and the effect of anticonvulsant medications.…”
Section: Cognitive Impairment Related To Seizure Disordersmentioning
confidence: 99%
“…A list of commonly used cognitive tasks and the areas of cognition they measure can be found in Table 1. The degree of impairment or lack thereof in children with epilepsy has been shown to be mediated by numerous factors, including age of onset, 1,2 seizure type, 1 duration of the seizure disorder, 1 the presence versus absence of visible underlying pathology, 3 responsiveness of seizure activity to treatment, 2,4 and the choice and amount of pharmacologic treatment used. 1,5 Because of the multitude of factors thought to contribute to cognitive decline of children with seizure disorders, it is often difficult to systematically investigate the effects of one factor while controlling for other variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 These children are also at a significantly increased risk of impairment in intellectual functions (ϳ3 times more likely to score outside normal limits on IQ tests and to develop a range of social and educational difficulties). [31][32][33] The experience of one episode of status epilepticus has been shown to lead to cognitive sequelae (defined as IQ Ͻ 80) in ϳ30% of cases. 34 Temporal lobe epilepsy has been particularly associated with impairments of language and memory function and with behavioral disorders.…”
Section: Introductionmentioning
confidence: 99%